Speculation of the Time-Dependent Change of FIB4 Index in Patients with Nonalcoholic Fatty Liver Disease: A Retrospective Study - Hiroshi Miyata; Satoru Miyata (Canadian Journal of Gastroenterology and Hepatology)
Aim. To speculate on the time-dependent change of FIB4 index in patients with nonalcoholic fatty liver disease (NAFLD) and its increase-decrease rate per year, simply and accurately. Methods. In all 23 patients with NAFLD with the value of FIB4 index over 1.30 at the peak, the period from the first to each examination date was calculated and this period (years) was regarded as x. Next, the mean value of FIB4 index during the past year to each examination date was regarded as y. In every y, the minimum and the maximum y value were found out. Between x corresponding to this minimum y and x corresponding to this maximum y, the correlation between x and y was analyzed as the main subject. Then, the slope of each correlation was investigated, because it should indicate increase-decrease rate per year. Results. In all 23 patients, the correlations as the main subject were recognized and the mean absolute value of correlation coefficient (r) was 0.91±0.08. As for the slope, the mean absolute value was 0.1371±0.1147 (/year). Conclusion. Simply and accurately, the time-dependent change of FIB4 index and its increase-decrease rate per year could be approximately speculated.